Paradox Havoc: time travel in Gothic Science Fiction - Rocatelli, Vinícius Bril [UNESP] (2023)
This research aims to analyze the paradoxes of time travel in Gothic Science Fiction in order to question our hypothesis: the Bootstrap Paradox is present in determinist tales of a more pessimistic vein, because the past cannot be changed, only perpetuated; the Grandfather Paradox, present in indeterminist tales of a more optimistic vein, because the past can be changed, therefore tragedies, for example, can be avoided or fixed. We will be looking at a myriad of different fictional texts from different mediums — short stories, novels, films, television, and video games. In particular: Hajime Isayama’s manga series Attack on Titan (2009-2021), Connie Willis’ novel To Say Nothing of the Dog (1998), two episodes of BBC’s Doctor Who (1963-1989; 2005-) — “The Day of the Doctor” (2013), and “Heaven Sent” (2015), Ken Levine’s Bioshock Infinite (2013), Tatsuya Matsubara’s Steins;Gate (2009), and James P. Blaylock’s Lord Kelvin’s Machine (1992). Therefore, the present research indulges in the practice of comparative literature. Likewise, we are going to be drawing from the critical writings of scholars such as Fred Botting, David Wittenberg, Brian Aldiss, Adam Roberts, James Gleick, and the like — specialists from the fields we are studying (time travel fiction, Science Fiction, and Gothic literature).